2009
DOI: 10.1093/jb/mvp197
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of the catalase-peroxidase (KatG) gene from a fast-growing Mycobacterium sp. strain JC1 DSM 3803

Abstract: The gene encoding a catalase-peroxidase (KatG) was cloned from chromosomal DNA of a fast-growing Mycobacterium sp. strain JC1 DSM 3803. The nucleotide sequence of a 5.7 kb EcoRI fragment containing the katG and its flanking regions was determined. The fragment (5,706 bps) contained two complete open reading frames (ORFs) encoding putative ferric uptake regulator A (FurA) and KatG proteins. The cloned gene, katG, had an ORF of 2241 nt, encoding a protein with calculated molecular mass of 81,748 Da. The furA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…For 5, a third band is observed at 369.00 nm, corresponding to a major contribution from phenyl ring π-π* internal transitions. As expected, spin-forbidden d-d bands were not observed in the spectra of the high-spin d 5 Mn(II) complexes presented in this work.…”
Section: Quantum Chemical Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For 5, a third band is observed at 369.00 nm, corresponding to a major contribution from phenyl ring π-π* internal transitions. As expected, spin-forbidden d-d bands were not observed in the spectra of the high-spin d 5 Mn(II) complexes presented in this work.…”
Section: Quantum Chemical Resultssupporting
confidence: 88%
“…Catalase-peroxidase (CP or KatG) is a heme protein that exhibits both catalase and peroxidase activities and plays a crucial role in defending against oxidative stress generated by aerobic oxygen metabolism or phagocytic attack from macrophages or neutrophils [5,6]. In MTB the KatG is responsible for the conversion of Mn(II) to Mn(III) in metalloenzymes containing manganese in active sites and has attracted special attention due to its participation in mycobacterial virulence [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This KatG exhibited typical enzymatic characters of mycobacterial KatGs and the antibodies raised against it strongly cross-reacted with other mycobacterial KatGs (Ro et al, 2003). Recently, we cloned a DNA fragment containing two complete open reading frames (ORFs) encoding a putative ferric uptake regulator A (FurA) and a putative KatG protein (Lee et al, 2010). Genetic analysis of the cloned furA and katG genes revealed that their gene organization and sequence homology were highly homologous to those of other mycobacteria.…”
mentioning
confidence: 99%
“…Two nested primers, Sod-NF (5 -CAGATCAACGAGCTTCACCA-3 ) and Sod-NR (5 -TAGTCCGCCTTCACGTTCTT-3 ), were synthesized to screen the previously constructed JC1 genomic cosmid library (Lee et al, 2010), based on the real JC1 partial SOD gene sequence identified above. The PCR screening was carried out in a 20 l reaction mixture containing 1 l of JC1 cosmid DNA, 50 pmol of each primer, and 1 unit of HotStar Taq plus DNA polymerase.…”
mentioning
confidence: 99%